2014
DOI: 10.2807/1560-7917.es2014.19.24.20833
|View full text |Cite
|
Sign up to set email alerts
|

Recent outbreaks of infectious syphilis, United Kingdom, January 2012 to April 2014

Abstract: Six outbreaks of infectious syphilis in the United Kingdom, ongoing since 2012, have been investigated among men who have sex with men (MSM) and heterosexual men and women aged under 25 years. Interventions included case finding and raising awareness among healthcare professionals and the public. Targeting at-risk populations was complicated as many sexual encounters involved anonymous partners. Outbreaks among MSM were influenced by the use of geospatial real-time networking applications that allow users to l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…In cities, such as London, Manchester and Brighton, syphilis is now endemic. However, in recent years, there have been a number of outbreaks reported outside of these urban areas 2. These clusters, occurring in areas with a relatively low background incidence, indicate the potential for outbreaks of syphilis wherever active sexual networks exist, particularly those which link out geographically and socially to established high-incidence MSM populations.…”
Section: Introductionmentioning
confidence: 99%
“…In cities, such as London, Manchester and Brighton, syphilis is now endemic. However, in recent years, there have been a number of outbreaks reported outside of these urban areas 2. These clusters, occurring in areas with a relatively low background incidence, indicate the potential for outbreaks of syphilis wherever active sexual networks exist, particularly those which link out geographically and socially to established high-incidence MSM populations.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological data, however, indicate that syphilis is still a relevant global health concern, with an estimated prevalence of 36 million individuals affected worldwide [ 3 ], and an incidence of >11 million new cases every year. Although the majority of syphilis cases occur in Latin America, sub-Saharan Africa, and South-East Asia [ 4 ], a resurgence of syphilis has been observed over the past decade in the US, Canada, Australia, China, and several European countries [ 5 , 6 , 7 , 8 , 9 , 10 ]. Furthermore, evidence that congenital transmission of this disease is a leading cause of stillbirths and perinatal deaths in developing areas [ 11 , 12 ], and that patients with syphilis are at increased risk for transmission and acquisition of HIV [ 13 , 14 ], also contributes to make syphilis an important global health problem.…”
Section: Introductionmentioning
confidence: 99%
“…Sexually transmitted infections (STI) continue to rise among gay men, bisexual men and other men-who-have-sex-with-men (MSM) in the United Kingdom (UK) [1–3]. Meeting sexual partners through geosocial networking apps, referred to as ‘dating apps’ hereafter, and social media [4] influences the transmission of STIs by increasing social networks, facilitating rapid partner change, disassortative mixing and, reducing the time for epidemics to spread [5–10]. Indeed, Beymer and colleagues found that use of dating apps for meeting sexual partners increased the likelihood of MSM testing positive for chlamydia and gonorrhoea compared to meeting partners through in-person methods [7].…”
Section: Introductionmentioning
confidence: 99%